2013
DOI: 10.2105/ajph.2012.301164
|View full text |Cite
|
Sign up to set email alerts
|

Early Childhood Lead Exposure and Academic Achievement: Evidence From Detroit Public Schools, 2008–2010

Abstract: Early childhood lead exposure was negatively associated with academic achievement in elementary and junior high school, after adjusting for key potential confounders. The control of lead poisoning should focus on primary prevention of lead exposure in children and development of special education programs for students with lead poisoning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(66 citation statements)
references
References 17 publications
2
60
0
Order By: Relevance
“…k = the number of variables in the index V ij = the jth socioeconomic position variable (Z-score) for a given census tract i V jDMA = mean of the jth variable in the three-county DMA S(V jDMA ) = standard deviation of the jth variable in the three-county DMA The DMA was divided into five levels (i.e., ranges of SEP) with cutoffs at the 20th, 40th, 60 th , and 80th percentiles (quintiles) of the CSI frequency distribution. 35 These levels permitted division of DMA census tracts of residence into five approximately equal proportions of the population in each group of socioeconomic status, i.e., very high socioeconomic position (VHSEP), high socioeconomic position (HSEP), middle socioeconomic position (MSEP), low socioeconomic position (LSEP), or very low socioeconomic position (VLSEP).…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…k = the number of variables in the index V ij = the jth socioeconomic position variable (Z-score) for a given census tract i V jDMA = mean of the jth variable in the three-county DMA S(V jDMA ) = standard deviation of the jth variable in the three-county DMA The DMA was divided into five levels (i.e., ranges of SEP) with cutoffs at the 20th, 40th, 60 th , and 80th percentiles (quintiles) of the CSI frequency distribution. 35 These levels permitted division of DMA census tracts of residence into five approximately equal proportions of the population in each group of socioeconomic status, i.e., very high socioeconomic position (VHSEP), high socioeconomic position (HSEP), middle socioeconomic position (MSEP), low socioeconomic position (LSEP), or very low socioeconomic position (VLSEP).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Zhang et al 35 evaluated the relationship between early childhood lead exposure and declines in academic achievement of Detroit Public School children from 2008 to 2010. Significantly, they found that children who had a BLL report of 910 μg/dL before they turned six were greater than twice as likely to score Bless than proficientô n academic achievement tests in reading, math, and science compared to those children who had a BLL report of G1 μg/dL.…”
Section: Introductionmentioning
confidence: 99%
“…2 Recent work by Aizer et al (2016), Zhang et al (2013), and Miranda et al (2007), nd detrimental e ects of childhood exposure to lead paint hazards on a number of education outcomes. 3 Beyond the e ects of lead pollution on child health and development, the presence of lead may impact neighborhoods through its capitalization in housing values and the sorting of residents to/away from homes with lead paint.…”
Section: Introductionmentioning
confidence: 99%
“…Pb, a potent neurotoxin, causes irreversible damage at BLLs below 5 µg/dL, including lowered IQ and decreased academic achievement (Canfield et al, 2003;Lanphear et al, 2000;Zhang et al, 2013) and increased rates of attention deficit disorders, depression and anxiety (Bouchard et al, 2009), and violent behaviors (Mielke and Zahran, 2012;Needleman, 2004). There is no safe level of exposure to Pb (Bellinger, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…This newly emerging urban lead exposure paradigm significantly alters the landscape of lead exposure prevention programs, placing the emphasis on addressing legacy lead sources in soils rather than leaded paint. The ubiquitous and non-point source nature of this exposure pathway necessitates a focus on primary prevention (Laidlaw et al, 2016;Lanphear et al, 2016;Needlemen 2004;Zhang et al, 2013) and primordial prevention (Leech et al, 2016) as the most viable strategies for reducing blood lead levels (BLLs) in urban children. Since the bioavailable fraction of lead in urban soils ultimately governs its public health burden, effective remediation schemes must reduce exposure to bioavailable lead fractions (Henry et al, 2015).…”
Section: Introductionmentioning
confidence: 99%